Sustainable value in the fashion industry: A case study of value construction/destruction using digital twins - Ralf Wagner; Agnieszka Kabalska (Sustainable Development, 2022)
New technologies—especially the emergence of digital fashion and a growing interest in creating digital twins (DTs)—are expected to alter existing value chains in the fashion industry as DT technology triggers a redesign of value creation processes. This qualitative case study demonstrates how and to what extent the development of DTs in the fashion industry addresses the sustainability needs of various stakeholders in both real-world and virtual-reality settings. The article examines the possibilities, benefits, and challenges of creating sustainable value in two distinct ways: traditionally, through physical processes, and through digital transformation by employing virtual processes via DTs. The main implication for further research is to examine the distribution of value facilitated by DT among heterogeneous stakeholders.
Keywords: 330; digital twin; fashion; sustainability; sustainable value; value creation